Bacterial Ring Rot of Potato - Sparks, Adam; Kennelly, Megan M. (Kansas State University, 2008)
Bacterial ring rot of potato, caused by the bacterium Clavibacter michiganensis subsp. sepedonicus, is a serious issue for seed potato production. This is a guide to controlling the bacterium.
EP150_2008-08
Keywords: EP150; Crops; Lawn and Garden; Health and Safety; EP